Assessing the impact and society response to online learning policy during the COVID-19 pandemic in Indonesia - Dwiputra, Rakadipta Septian; Ayuputri, Ikacipta Mega (Jurnal Pendidikan, Sains Sosial, dan Agama, 2025)
In response to the COVID-19 pandemic, the Indonesian Government implemented a policy mandating online learning activities to replace conventional education during the peak of the virus spread. This article employs descriptive analysis using secondary data and big data analytics from social media data to examine the pandemic's immediate effects and impacts on achieving Sustainable Development Goals (SDGs) number 4, focusing on quality education. While positive sentiments surround the implementation of online learning in Indonesia, the study reveals negative trends and a slowdown in achieving critical indicators related to SDG 4. The findings highlight the need for the Indonesian government to formulate and implement improved policies to reach the Quality of Education targets by 2030. This study provides valuable insights into the progress and challenges within the Indonesian education system, offering policymakers the necessary information to make informed decisions for advancing education in the country. Keywords: COVID-19, online learning, Sustainable Development Goals (SDGs), social media data